Asymmetric metallicity patterns in the stellar velocity space with RAVE - Antoja, Teresa; Grebel, Eva K. (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics